CALCULATION OF SHORTENING DUE TO OUTCROP-SCALE DEFORMATION AND ITS RELATION TO REGIONAL DEFORMATION PATTERNS - Hogan J.P.; Dunne W.M. (My University, 2001)
The objectives of this study are to: assess the regional contribution of outcrop-scale structures in well-exposed rocks of a tectonic province; and evaluate how failure to measure this scale of structure affects the assessment of regional deformation. The contribution of outcrop-scale structures to regional deformation has not been quantified previously because of the need for long continuous exposures to regionally characterize the structures. This study used 18.6km of semi-continuous roadcut and streambed exposures in well-exposed Devonian clastic rocks to construct 1:200-scale profiles to address the objectives.Key results are: (1) outcrop-scale structures contribute about 1/6 to 1/4 of total regional shortening. (2) Submapscale shortening components from microscale and outcrop-scale structures equal mapscale shortening that would be interpreted from a regional cross-section. (3) Analysis of submapscale structures in the target blind thrust belt is needed to identify that the roof-sequence deformation preceded and continued through duplex formation. (4) The kinematic response of the roof sequence would be incorrectly identified as backthrusting if the shortening contribution of outcrop-scale structures is ignored. (5) Although measured outcrop-scale shortening does not match that predicted by the fractal analysis of other workers, the fractal approach to predicting deformation as a function of scale may still be valid.
Keywords: SHORTENING; OUTCROP-SCALE DEFORMATION; TECTONIC PROVINCE; Devonian; Paleozoic::Devonian; Палеозой::Девонская